Korean Pentecostalism and Shamanism: Developing Theological Self-understanding in a Land of Many Spirits - Kim, Kirsteen (PentecoStudies, 2017)
The background to this article is the controversy caused in 1980s South Korea when some theologians accused Yonggi Cho's Full Gospel theology of syncretizing shamanism with Christianity. In this article, I shall problematize the use of both shamanism and Pentecostalism in this controversy. Instead, I shall set the episode in the wider context of what might be called Korean traditional religion, which has an animistic cosmology. By pointing to an affinity between Korean Protestantism more generally and Korean traditional religion that goes back at least to the 1907 Korean Revival, I shall argue that the Pentecostal-Charismatic and the liberationist strands of Korean Protestantism together represent a developing understanding of what it means to do Christian theology in the context of animism - or in a land of many spirits.